Biometry, the safe key - Fraile Hurtado, María; Herrero Langreo, Miguel; Menéndez de Miguel, Pilar; Delgado Villanueva, Valerio (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2019)
Biometry is the next step in authentication, why do not we take this stepforward in our communication security systems? Keys are the main disadvantage in the cryptography, what if we were our own key?
Keywords: biometry; cryptography; iris; security; IJIMAI